2008
DOI: 10.1038/sj.onc.1211020
|View full text |Cite
|
Sign up to set email alerts
|

Runx2-mediated activation of the Bax gene increases osteosarcoma cell sensitivity to apoptosis

Abstract: The Runx family of transcription factors regulate cell growth and differentiation, and control the expression of target genes involved in cell fate decisions. We examined the role of the bone-related member of this family, Runx2, in regulating apoptosis via modulation of the Bcl2 family of genes in the osteosarcoma cell line Saos2. Our data demonstrate that Runx2 directly binds to two Runxspecific regulatory elements on the human bax promoter thereby inducing Bax expression. Furthermore, bone morphogenetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
7
52
2
Order By: Relevance
“…Recent work has suggested that after treatment of SaOs-2 cells with BMPs, RUNX2 might directly activate the proapoptotic gene Bax (with no change in Bcl2 expression). (13) Our experiments in hMSCs gave similar results; in FCS-free medium, TNF-a induced a strong increase in Bax but did not modify Bcl-2 expression. When RUNX2 was inhibited by siRNA, no change in Bax expression was observed after TNF-a treatment.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Recent work has suggested that after treatment of SaOs-2 cells with BMPs, RUNX2 might directly activate the proapoptotic gene Bax (with no change in Bcl2 expression). (13) Our experiments in hMSCs gave similar results; in FCS-free medium, TNF-a induced a strong increase in Bax but did not modify Bcl-2 expression. When RUNX2 was inhibited by siRNA, no change in Bax expression was observed after TNF-a treatment.…”
Section: Discussionsupporting
confidence: 77%
“…It is also important to note the suggestion by Bellido and colleagues (45) that the antiapoptotic effects of parathyroid hormone (PTH) might require RUNX2-a position that appears to contradict the study by Eliseev and colleagues (13) and that work. However, these antiapoptotic effects are short-lived because PTH itself stimulates the proteasomal degradation of RUNX2.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(26,27,33) In order to determine the functions of HDAC4 and HDAC5 in the Runx2-mediated suppression of Notch1 signaling, we performed a transcription reporter assay using HDAC4 and HDAC5. The transcriptional activity of Notch1-IC was repressed in Runx2-expressing cells, and the Runx2-induced suppression of Notch1 transcriptional activity was restored via the coexpression of HDAC4 and HDAC5 (Fig.…”
Section: Runx2 Inhibits Notch1 Transcriptional Activitymentioning
confidence: 99%
“…(25,(28)(29)(30) Recently, multiple biologic functions of Runx2 have been demonstrated in various cell types, including chondrocytes, endothelial cells, osteosarcoma cells, T-cell lymphomas, and breast cancer cells. (31)(32)(33)(34)(35) One of the central players in the osteoblast differentiation process is the Runx2 transcription factor, which coordinates multiple signals involved in osteoblast differentiation. Up to the present, several regulators such as Stat1, Twist, Hey1, and Notch1 have been shown to form inhibitory complexes with Runx2 and to inhibit osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%